Real design practice, real design computation. (March 2021) - Wang, Zichu Will
The business model of architecture has been accused of being technologically deficient. Through case studies, this paper investigates alternatives to the status quo of computation in architecture, with a focus on design-oriented service providers. It first examines the discourse on computation within the field, then describes the experiments of a relevant design firm before discussing implications for the wider industry. In the process, the paper articulates the gap between theoretical computing applications and the realities of the architecture business. It addresses difficult technological adaptations within the industry with concrete use cases of integrated computing expertise, highlighting opportunities, benefits, and, more importantly, the need for a computational workforce.